Heat and drought stresses in wheat (Triticum aestivum L.): Substantial yield losses, practical achievements, improvement approaches, and adaptive mechanisms - Zulkiffal, Muhammad; Ahsan, Aneela; Ahmed, Javed; Musa, Muhammad; Kanwal, Amna (IntechOpen, 2021)
The major wheat-producing countries have heterogeneous and fragile agro climatic surroundings but frequently restraining wheat yield and quality losses are predominant under heat and drought prone agriculture exclusively when both stresses occur in blend, which looms the food security globally. However, many suggested examples are available in these countries for the mitigation of these two stresses by using different conventional and modern improvement and agronomic approaches. In addition to these approaches, morphological, physiological, anatomical, biochemical, phenological, and physiochemical vicissitudes, which trigged during these stresses, have also been elucidated. There complete deliberation in combination for wheat improvement is still a contest, but a win-win option is a holistic attitude in future.